Efektivitas advertising, brand image, dan harga kompetitif terhadap keputusan pembelian mie instan merek XYZ di Kabupaten Gresik - Prahara, Lintang Heydi; Sukaris, Sukaris (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
The aim of this research is to study consumer behavior based on purchasing decisions. Based on observations in the literature, advertising, brand image, and competitive prices are components that make consumers decide what to buy. There are 150 respondents for this type of quantitative survey research. Consumers in the Gresik Regency area who have purchased or are currently consuming XYZ brand instant noodles were given a questionnaire as part of the data collection process. Hypothesis testing is made possible by multiple linear regression methodology in this study. Research findings show that in the Gresik area, advertising does not have a significant effect on purchasing XYZ brand instant noodles. Meanwhile, brand image and competitive prices have a significant influence on the decision to purchase instant noodle brand XYZ. Purchasing decision variables are influenced significantly, both partially and jointly, by advertising, brand image and competitive price variables. Future developments in this research could consider three main factors: advertising, brand image, and competitive pricing. For more comprehensive research, other variables such as product quality and psychological factors that influence purchasing decisions can also be included to provide more important contributions regarding this area of research.